Introduction to qualitative research methods : a guidebook and resource - Taylor, Steven J. ; Bogdan, Robert ; DeVault, Marjorie L. (John Wiley and Sons, Inc, 2020)
Among the people: how to conduct qualitative research --Introduction: go to the people --Note on the history of qualitative methods -- Qualitative methodology -- Theory and methodology -- Notes -- Research design and pre-fieldwork -- Research design -- Selecting settings -- Obtaining institutional review board approval -- Writing proposals -- Access to organizations -- Access to public and quasi-public settings -- Access to private settings --What do you tell gatekeepers and informants? -- Collecting data about obtaining access --Covert research -- Participant observation: in the field -- Entering the field -- Negotiating your role -- Establishing rapport -- Participation -- Key informants -- Difficult field relations -- Forming relationships -- Field tactics -- Asking questions -- Learning the language